Analysis of Green Marketing Strategies on Consumer Choices with a Marketing Mix Approach at The Body Shop Makassar City - Basri Bado; Samirah Dunakhir (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze the influence of green marketing strategies on customer choices for the Makassar Body Shop cosmetics company. The problem in this research is that there is a research gap regarding green marketing strategy, which is a potential strategy as a business strategy and has been used as a marketing strategy pivot. The collection method in this research was carried out using a survey method, namely by using a questionnaire. The research population was customers of the cosmetics company The Body Shop in Makassar, with a sample size of 150 people. The sampling method used in this research is the census method which uses all members of the population as research samples. Testing of the hypothesis in this research will be carried out in a multivariate manner using logistic regression. Logistic regression is used because the independent variable is a combination of metric and nominal (non-metric). The results of the analysis show that the variables price, product, place and gender influence customer choices. Meanwhile, promotion variables, age, education and income have no effect on customer choices. The main implication is that The Body Shop must pay attention to quality aspects to balance high prices and women as its main market.